PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ADOBE FLASH CS6 UNTUK SISWA KELAS IV SD/MI - Nur Kamelia; Sugiyono Sugiyono; Hery Kresnadi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2020)
AbstractThe purpose of this research is to develop a interactive learning media based on Adobe Flash Cs 6 for a Thematic subject. Development uses Adobe Flash Cs 6 software to produce interesting learning media equipped with animations, images, videos, and sound. This research and development used and modificated the Borg And Gall development design model. A sample group that is used for this researcah is ten primary students in forth level from Primary School of 24 Teluk Durian. In addiction, the apparatuses for this research consist of a questionnaire for expert validity and response by student in content as well as techincal method. A quality evaluation result of a interactive learning media by the experts has a good value 4,70 its in a very good rate. Also, The result of research discovers that a interactive learning media also has a very good value 4,28 and 4,40. In conclusion, this a interactive learning media for a Thematic subject is has a very good quality that could be used by the forth level of primary students.